The Role of Radio in Information Dissemination in the Digital Age - Haspiaini, Nurhasanah; Widianti, Mira Aditia (Communicatus: Jurnal Ilmu komunikasi, 2026)
Radio is a mass media that has a role in spreading messages (news, information, entertaiment) with audio broadcasts. However, the drawback of radio is that it cannot be seen, so it is a fleeting medium, heard only once, and cannot be repeated. The lack of radio can overcome new media innovation, namely with the existence of podcasts. Radio as an electronic mass media that has long existed tries to remain a medium that capable of spreading information in an all-digital era with podcasts. Essentially, the radio is responsible for disseminating information on an audio basis. The superior value of radio is radio listeners and radio stations have a close relationship. With sound, the listener can be imaginative (theater of mind). In this case, private radio stations such as Motion Radio select their digital content or podcast content. In this case, radio stations such as Motion Radio select their podcast content. Not all of the content delivered during live radio broadcasts becomes podcast content. They choose content that is more informative for listeners than just entertainment content. This is what makes Motion Radio show its role as a radio that spreads information in today's digital era. This study examines the podcast content produced by Motion Radio during live broadcasts and how it is managed. Data is taken from the results of interviews with the producers of Motion Radio. This study uses a qualitative descriptive analysis. This research seeks to reveal the role of radio in disseminating information in the digital content era through podcasts.